MicroRNA-22 inhibits proliferation and promotes differentiation of satellite cells in porcine skeletal muscle - Hong Quyen DANG; Gu-li XU; Lian-jie HOU; Jian XU; Guang-liang HONG; Chingyuan HU; Chong WANG (Journal of Integrative Agriculture)
Pig is an important economic animal in China. Improving meat quality and meat productivity is a long time issue in animal genetic breeding. MicroRNAs (miRNAs) are short non-coding RNAs that participate in various biological processes, such as muscle development and embryogenesis. miR-22 differentially expresses in embryonic and adult skeletal muscle. However, the underlying mechanism is unclear. In this study, we investigated miR-22 function in proliferation and differentiation of porcine satellite cells (PSCs) in skeletal muscle. Our data show that miR-22 expressed in both proliferation and differentiated PSCs and is significantly upregulated (P<0.05) during differentiation. After treated with the miR-22 inhibitor, PSCs proliferation was significantly increased (P<0.05), as indicated by the up-regulation (P<0.01) of cyclin D1 (CCND1), cyclin B1 (CCNB1) and down-regulation (P<0.05) of P21. Conversely, over-expression of miR-22 resulted in opposite results. Differentiation of PSCs was significantly suppressed (P<0.05), evidenced by two major myogenic markers: myogenin (MyoG) and myosin heavy chain (MyHC), after transfecting the PSCs with miR-22 inhibitor. Opposite results were demonstrated in the other way around by transfection with miR-22 mimics. In conclusion, the data from this study indicated that miR-22 inhibited the PSCs proliferation but promoted their differentiation.